THE IMPACT OF QUALITY MANAGEMENT SYSTEM ON THE PRODUCT QUALITY OF THE MANUFACTURING INDUSTRY IN PAKISTAN - Muhammad Azeem Ahmad; Arshia Hashmi; Waris Ali (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The present study aims to investigate the impact of quality management system on information quality and information quality impact on design, operating, and environmental performance. These performances impact the product quality of the manufacturing companies in Pakistan. The examination of mediating role of design performance, operating performance, and environmental performance among the links of information quality and product quality is also included in the objectives of the current research. This study has executed the quantitative methods and used the questionnaires to obtain the data from respondents and also used the smart-PLS to examine the relationships between the variables. The results exposed that a quality management system has a positive impact on the information quality, and information quality also has a positive impact on the design, operating, and environmental performance, and these performances also have a positive impact on the product quality. The results also exposed that design performance operating performance and environmental performance have positively mediated the links among the information quality and product quality. This study is suitable for the regulators who want to develop regulations related to the quality management system that could increase the product quality.